Molecular iodine-promoted oxidative cyclization for the synthesis of 1,3,4-thiadiazole-fused- [1,2,4]-thiadiazole incorporating 1,4-benzodioxine moiety as potent inhibitors of α-amylase and α-glucosidase: In vitro and in silico study - Hussain, Rafaqat; Shah, Mazloom; Iqbal, Shahid; Rehman, Wajid; Khan, Shoaib; Rasheed, Liaqat; Naz, Haseena; Al-ghulikah, Hanan A.; Elkaeed, Eslam B.; Pashameah, Rami Adel; Alzahrani, Eman; Farouk, Abd-ElAziem (Frontiers in Chemistry, 2022)
Twenty-five analogues were synthesized based on 1,3,4-thiadiazole-fused-[1,2,4]-thiadiazole incorporating 1,4-benzodioxine moiety (1-25) and then tested for the anti-diabetic profile. The entire afforded derivatives showed varied inhibition profiles ranging between 0.70 ± 0.01 to 30.80 ± 0.80 µM (against α-amylase) in comparison to standard acarbose (12.80 ± 0.10 µM). Similarly synthetics analogues also displayed varied range of α-glucosidase activity ranging from 0.80 ± 0.01µM to IC50 = 29.70 ± 0.40 µM (against α-glucosidase) as compared to standard acarbose (IC50 = 12.90 ± 0.10 µM). Among synthetic scaffolds, compound 22 was shown excellent potency due to the presence of di-hydroxy substitutions at 2,3-position of the aryl ring. The structure-activity relationship was carried out for all analogues based on substitutions pattern around the aryl ring and further, the potent scaffolds were subjected to molecular docking study to check out how active residues of targeted enzymes interact with active parts of newly prepared analogues and the result obtained shows that these compounds furnish several key interactions with enzyme active site and hence enhanced their enzymatic activities.